AXL receptor tyrosine kinase modulates gonadotropin-releasing hormone receptor signaling - Pardis Mohammadzadeh; Mina Roueinfar; Gregory C. Amberg (Cell Communication and Signaling, 2023)
Abstract Background Gonadotropin-releasing hormone (GnRH) receptors are essential for reproduction and are expressed in numerous urogenital, reproductive, and non-reproductive cancers. In addition to canonical G protein-coupled receptor signaling, GnRH receptors functionally interact with several receptor tyrosine kinases. AXL is a receptor tyrosine kinase expressed in numerous tissues as well as multiple tumors. Here we tested the hypothesis that AXL, along with its endogenous ligand Gas6, impacts GnRH receptor signaling. Methods We used clonal murine pituitary αT3-1 and LβT2 gonadotrope cell lines to examine the effect of AXL activation on GnRH receptor-dependent signaling outcomes. ELISA and immunofluorescence were used to observe AXL and GnRH receptor expression in αT3-1 and LβT2 cells, as well as in murine and human pituitary sections. We also used ELISA to measure changes in ERK phosphorylation, pro-MMP9 production, and release of LHβ. Digital droplet PCR was used to measure the abundance of Egr-1 transcripts. A transwell migration assay was used to measure αT3-1 and LβT2 migration responses to GnRH and AXL. Results We observed AXL, along with the GnRH receptor, expression in αT3-1 and LβT2 gonadotrope cell lines, as well as in murine and human pituitary sections. Consistent with a potentiating role of AXL, Gas6 enhanced GnRH-dependent ERK phosphorylation in αT3-1 and LβT2 cells. Further, and consistent with enhanced post-transcriptional GnRH receptor responses, we found that Gas6 increased the abundance of Egr-1 transcripts. Suggesting functional significance, in LβT2 cells, Gas6/AXL signaling stimulated LHβ production and enhanced GnRH receptor-dependent generation of pro-MMP9 protein and promoted cell migration. Conclusions Altogether, these data describe a novel role for AXL as a modulator of GnRH receptor signaling. Video Abstract